PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN INDUSTRI MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - Arif Oktianto, Bima (Universitas muhammadiyah palembang, 2017)
The present study aims to investigate the influence of financial performanceof the stock prices on food and beverage industries in the Indonesia StockExchange that are Current Ratio (CR), Debt to Equity Ratio (DER), TotalAssets Turnover (TATO), and Net Profit Margin (NPM).This study usedsecondary data that obtained from the financial statements of IndonesianCapital Market Directory (ICMD) based on the publication of the IndonesiaStock Exchange. The sample used in this study were enterprises food andbeverage industries listed in the Indonesia Stock Exchange in 2011 – 2015.The data were analyzed by using multiple linear regression analysis.Theresults of this study indicated that there was significant effect simultaneouslybetween financial performance [Current Ratio (CR), Debt to Equity Ratio(DER), Total Assets Turnover (TATO), and Net Profit Margin (NPM)] towardthe stock prices on food and beverage industries in Indonesia stockExchange in 2011 - 2015. While partially showed that of the fourindependent variables, which indicated the presence of significant influencewere Current Ratio (CR), Total Assets Turnover (TATO), and Net ProfitMargin (NPM) to the stock prices on food and beverage industries inIndonesia stock Exchange in 2011-2015.